Influence of nanosized silica particles on the rheological behaviour of the lyotropic hexagonal phase of Glucopone surfactant - Siddig, Mohamed Ahmed; Radiman, S.; Jan, L.S.; Muniandy, S.V. (2005)
The effect of nanosized silica particles on the rheological behaviours and Structures of the hexagonal liquid crystalline phases of Glucopone/water/heptane system were investigated. The surfactant used is technical grade alkyl polyglucoside (APG) with commercial name Glucopone 215 CSUP. Small-angle X-ray scattering (SAXS) and polarizing microscopy were used for phase identification and structure characterizations. SAXS scattering profiles showed characteristics of the hexagonal phases before and after the addition of silica particles. The area per surfactant molecule was found to decrease as the silica concentration was increased. The samples exhibited shear thinning behaviour. with the effect of the silica particle concentrations to be more profound in the dynamic viscosity than the shear viscosity. The frequency-dependent moduli were found to be characteristic of the hexagonal phase in the linear viscoelastic region. The increase in the elasticity with increasing silica particle concentrations was attributed to the strength of network and the formation of smaller structure as indicated by SAXS measurements. The melting transition of the hexagonal phase for different concentrations of silica particles was found to be around 53 degreesC. The elastic modulus and viscosity appeared to decrease with increasing temperature and the crossover between G' and G" occurred at higher frequency, indicating reduction in the relaxation time. The change in the slopes of G' and G" versus temperature confirmed structural changes that were observed from shear viscosity measurements. The effect of silica particles on the rheological behaviour was more pronounced as the concentration was increased. The results showed strong Correlation between rheology and microstructural changes in the dispersion of nanoparticle silica in the hexagonal phase system. (C) 2004 Elsevier B.V. All rights reserved.